Differences in richness and composition of gastrointestinal parasites of small rodents (Cricetidae, Rodentia) in a continental and insular area of the Atlantic Forest in Santa Catarina state, Brazil Diferenças na composição e na riqueza de parasitas gastrointestinais de pequenos roedores (Cricetidae, Rodentia) em uma área continental e uma insular de Floresta Atlântica em Santa Catarina, Brasil - VV. Kuhnen; ME. Graipel; CJC. Pinto (Brazilian Journal of Biology, 2012)
The first and only study on gastrointestinal parasites of wild rodents in the Island of Santa Catarina was done in 1987. The aim of this study was to identify intestinal parasites from wild rodents in Santo Amaro da Imperatriz and Santa Catariana Island, and to compare the richness and composition of the gastrointestinal parasite community of both areas. Rodents were captured with live traps, and feces were screened using the sedimentation method and optical microscopy. The following species of rodents were captured in the two areas: Akodon montensis, Euryoryzomys russatus, Oligoryzomys nigripes and Nectomys squamipes. In Santo Amaro da Impetratriz, prevalent parasites were: A. montensis (51%), E. russatus (62%), O. nigripes (53%) and N. squamipes (20%). From the Island of Santa Catarina the rodent prevalence rates were: A. montensis (43%), E. russatus (59%), O. nigripes (30%) and N. squamipes (33%) and the collected parasites were: Hymenolepis sp., Longistriata sp., Strongyloides sp., Hassalstrongylus sp., Syphacia sp., Trichomonas sp., Ancylostomidae, Trichuridae, Oxyuridae and Eucoccidiorida. The species richness (10.6 ± 0.7) of the endoparasite comunity in the area located on the continent was higher (p < 0.01) and different (p = 0.001) from that of the area located on the island (6.9 ± 0.5). Parasitas gastrointestinais de roedores silvestres foram estudados pela primeira vez na Ilha de Santa Catarina em 1987. Desde então, nenhum outro estudo nessa área foi realizado no Estado. O objetivo do presente estudo foi identificar parasitas intestinais de roedores silvestres de Santo Amaro da Imperatriz e da Ilha de Santa Catarina, bem como comparar a composição e a riqueza da comunidade de parasitas gastrointestinais de ambas as áreas. A análise das fezes dos animais capturados foi realizada por meio do método de sedimentação espontânea (HJP) e por microscopia óptica. Nas duas áreas, foram capturadas as espécies de roedores Akodon montensis, Euryoryzomys russatus, Oligoryzomys nigripes e Nectomys squamipes. Em Santo Amaro da Impetratiz, observou-se a seguinte prevalência de parasitoses: A. montensis (51%), E. russatus (62%), O. nigripes (53%) e N. squamipes (20%). Diferentemente, em Florianópolis, as frequências de parasitoses foram: A. montensis (43%), E. russatus (59%), O. nigripes (30%) e N. squamipes (33%). Os parasitos encontrados pertencem aos grupos: Hymenolepis sp., Longistriata sp., Strongyloides sp., Hassalstrongylus sp., Syphacia sp., Trychomonas sp., Ancilostomatidae,Trichuridae, Oxyuridae e Eucoccidiorida. Foi possível observar que os roedores da área localizada no continente (Santo Amaro da Imperatriz) possuem uma comunidade de parasitas gastrointestinais mais rica (10.6 ± 0.7; p < 0.01) e diversa (p = 0.001) do que a comunidade presente na Ilha de Santa Catarina (6.9 ± 0.5).